(untitled) (Research, Society and Development, 2021)
Aiming at promoting safe practices and generating indicators for monitoring and evaluating the process of drug use, the objective of this work was to identify the prescription and dispensing errors avoided by the pharmaceutical team in order to contribute to the quality of the service. This is a cross-sectional analysis carried out at the central pharmacy in a teaching hospital from January 1st to December 31th, 2019. The records of pharmaceutical operations and the checking of medications before dispensing were obtained. The collected data produced indicators that were analyzed using the Pareto Diagram and compared with the events notified at the institution. The most frequent prescription errors avoided by pharmaceutical intervention was the frequency and the inadequate dose. The errors prevented during the checking of the medication packages were the lack of a prescribed medication and a change of schedule. In addition, from notifications related to medication errors, it was observed that 32.88% were related to prescription errors, 41.10% to dispensing errors and 26.03% to administration errors. Even with underreporting, 3343 events prevented by the pharmaceutical team were recorded, showing that their performance is essential and is part of the strategies for preventing adverse events in the hospital environment.